Cytomegalovirus colitis mimicking rectal carcinoma in an immunocompetent elderly woman. (10th May 2016) - Chidlovskii, Elena; Deroux, Alban; Bernard, Sylvain; Couturier, Pascal
Abstract : Cytomegalovirus (CMV) colitis is uncommon in immunocompetent patients, despite a high seroprevalence rate of CMV in the general population. CMV infection has been described in individuals with compromised immune systems: in AIDS, under corticosteroid and immune modulating treatment, with cancer or haematological malignancies. Its most frequent clinical presentation is a necrotising ulcerative form; pseudotumoural CMV colitis has been described as highly exceptional. We report a case of CMV colitis mimicking rectal carcinoma in an immunocompetent elderly woman. The immunosenescence and protein-energy malnutrition increase incidence and severity of infectious diseases in elderly individuals. Immunosenescence may affect all aspects of immunity; severe protein malnutrition modifies mostly cellular immunity, growing susceptibility to infections.